Spontaneous Conception during In Vitro Fertilization prior to Embryo Transfer without the Opportunity for Preimplantation Genetic Testing - Brindha Bavan; Amin A. Milki (Case Reports in Obstetrics and Gynecology)
In addition to the potential for multiple pregnancy, spontaneous conception during in vitro fertilization (IVF) can lead to undesired genetic outcomes. We present a case of a patient undergoing IVF with the intention of subsequent frozen embryo transfer after preimplantation genetic testing (PGT). Unprotected intercourse 6 days prior to egg retrieval resulted in a spontaneous pregnancy before the opportunity for embryo transfer. This case report highlights that spontaneous conception during IVF compromises the ability to transfer embryos that are euploid, unaffected by single gene disorders, or intended for gender balancing within a family when desired.